Brain-based learning : possible applications to English Language classes / Rofiza Aboo Bakar, Aznizah Hussin and Rohana Atan - Hussin, Aznizah; Atan, Rohana; Aboo Bakar, Rofiza (Universiti Teknologi MARA, Pulau Pinang & Pusat Penerbitan Universiti (UPENA), 2012)
Brain-based learning is a learning approach that caters to ways that the human brain learns best and may enable teachers and learners make smart decisions about their teaching experiences and learning processes. This paper explains briefly about the parts of the human brain, brain-based learning theory, and offers suggestions on how that theory may be integrated with English language classes. The importance of emotion for an optimal learning is discussed. Applications of its roles based on ideas put forth by experts in this brain-based field and experiences of a few English teachers who exercised these ideas are also presented.